"Expect the unexpected"? LDC GATS commitments as internationally credible policy indicators? The example of Mali - Dale Honeck (World Trade Organization (WTO), 2011)
There is a stark contrast between the ambitious investment promotion efforts of many least developed countries (LDCs) and their often minimal commitments under the General Agreement on Trade in Service (GATS). At a time of urgent need to address domestic infrastructure and investment gaps, this situation cannot be a positive signal for investors (either domestic or foreign), and may be a missed opportunity to address services aspects of the Millennium Development Goals (MDGs). LDCs often lack internationally credible mechanisms for making commitments, which contributes to their evident difficulty in attracting the more employment-generating types of investment that could bring greater opportunities for poverty alleviation. Considering that most LDCs, under domestic laws, have already opened a wide range of services sectors to foreign direct investment (FDI), there may be an opportunity to enhance the international consistency and credibility of LDC investment promotion efforts by making GATS commitments, while preserving substantial policy space with regard to the actual status quo. While reforms to domestic regulations are undoubtedly of greater importance to attracting FDI, GATS commitments, including partial commitments, can be used to publicize LDC investment priorities in services (such as attracting new businesses, encouraging joint ventures and technology transfer, etc.), and make them legally binding internationally. Offers to make new GATS commitments can further be used as bargaining chips in the current Doha Development Agenda (DDA) negotiations. Mali has been selected as a case study, due to the fact that trade and investment policies are clearly and consistently documented.
Keywords: F13; F14; I38; L80; L90; O14; O19; O24; O55; P45; 330; LDCs; GATS; FDI; policy credibility; MDGs; policy space; Mali; Africa; investment promotion; poverty alleviation; GATS; Direktinvestition; Glaubwürdigkeit; Vierte Welt